The use of QR code on educational domain: a research and development on teaching material - Firmansyah, Guntur; Hariyanto, Didik (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
The study aims at designing and developing QR code-based teaching materials for the theory and the practice session of the course Table Tennis that might be easily and readily accessed and learned in order to improve the motivation and the basic skills in playing table tennis. Therefore, the nature of the study is research and development. Within the research and development, the researcher has adopted the 4D model proposed by Thiagarajan et al. The stages in the 4D model consist of Define, Design, Develop and Disseminate. In brief, the data that have been gathered within the study are as follows: (1) in the needs analysis, 79.20% of the total students that have been surveyed state that they agree with the development of QR code-based teaching materials for the course Table Tennis; (2) in the development stage that has gone through the validation test by 3 evaluators, the learning media expert states that the product has been 75.00% valid, the material expert states that the product has been 85.20% ready and the linguistic expert states that the product has been 75.00% valid; and (3) within the experiment test, the validity has been 77.01%. Therefore, it might be concluded that the QR code-based teaching materials are already feasible and ready for implementation.